Variation in floral volatiles across time, sexes, and populations of wind‐pollinated Schiedea globosa. Issue 2 (22nd February 2022) - Powers, John M.; Sakai, Ann K.; Weller, Stephen G.; Campbell, Diane R.
Abstract: Premise: Floral scent is a key aspect of plant reproduction, but its intraspecific variation at multiple scales is poorly understood. Sexual dimorphism and temporal regulation of scent can be shaped by evolution, and interpopulation variation may be a bridge to species differences. We tested whether intraspecific chemical diversity in a wind‐pollinated species where selection from biotic pollination is absent is associated with genetic divergence across the Hawaiian archipelago. Methods: Floral volatiles from females, males, and hermaphrodites of subdioecious Schiedea globosa grown in a common environment from 12 populations were sampled day and night and analyzed by gas chromatography–mass spectrometry. Variation among groups was analyzed by constrained ordination. We also examined the relationships of scent dissimilarity to geographic and genetic distance between populations. Results: Flowers increased total emissions at night through higher emissions of several ketones, oximes, and phenylacetaldehyde. Females emitted less total scent per flower at night but more of some aliphatic compounds than males, and males emitted more ketones and aldoximes. Scent differed among populations during day and night. Divergence in scent produced at night increased with geographic distance within 70–100 km and increased with genetic distance for males during the day and night, but not for females. Conclusions: Schiedea globosa exhibits diel and sex‐based variation in floral scent despite wind pollination and presumed loss of biotic pollination. In males, interpopulation scent differences are correlated with genetic differences, suggesting that scent evolved with dispersal within and across islands.